Tax Sanctions In Paying Land And Building Taxes - Wijana, I Made Dauh; Yuesti, Anik; Bhegawati, Desak Ayu Sriary; Yanti, Kadek Eryn Mega (The journal of contemporary issues in business and government, 2021)
This study aims to determine the effect of the tax object value (TOV), taxpayer attitudes, taxpayer awareness, tax knowledge, and Tax Returns Payable (TRP) on taxpayer compliance in paying land and Land and Building Taxes with tax penalties as moderating variable at North Denpasar District. This research uses primary data and secondary data. The number of samples in this research is 100 respondents with the sampling method usingaccidental sampling method. Data collection is done through documentation and questionnaire. Technical data analysis of his study using moderated regression analysis (MRA). The results of this study shows that the tax object value (TOV) has positive and significant effect on taxpayer compliance, taxpayer attitude has positive and significant effect on taxpayer compliance, taxpayer awareness has no significant effect on taxpayer compliance, tax knowledge has positive and significant effect on taxpayer compliance, TRP has no significant effect on taxpayer compliance, tax penalties can moderating the effect of the tax object value (TOV) on taxpayer compliance, tax penalties can not moderating the effect of taxpayer attitude on taxpayer compliance, tax penalties can not moderating the effect of taxpayer awareness on taxpayer compliance,